Serum Pyridinoline is Associated With Radiographic Joint Erosions in Rheumatoid Arthritis - Abu Mansor Matardiah NOR HASHIMAH; Rajalingham SAKTHISWARY; Syahrul Sazliyana SHAHARIR; Asrul WAHAB (Archives of Rheumatology, 2019)
Objectives: This study aims to compare the serum pyridinoline (Pyd) levels between rheumatoid arthritis (RA) patients and healthy controls and to determine the correlation of serum Pyd levels with radiographic joint erosions. Patients and methods: Serum samples were obtained from 48 patients with RA (9 males, 39 females; mean age 60.5 years; range 54 to 64 years) and 48 healthy controls (9 males, 39 females; mean age 57.5 years; range, 47 to 65 years). The enzyme-linked immunosorbent assay method was used for quantitative analysis of serum Pyd. Besides, all RA patients were assessed for joint damage based on modified Sharp score, disease activity based on disease activity score in 28 joints and functional capacity based on health assessment questionnaire-disability index. Results: The median serum Pyd levels were significantly higher among the RA patients (110.20 ng/mL [92.30-120.64]) compared to the controls (98.22 ng/mL [85.54-111.41]); p<0.05. RA patients with erosive disease had significantly higher serum Pyd levels (p=0.024). There was a significant positive correlation between serum Pyd levels and joint erosion score (r=0.285, p=0.049). The serum Pyd levels had no demonstrable association with disease activity or functional capacity. Steroid therapy did not appear to influence the levels of serum Pyd. Conclusion: Rheumatoid arthritis patients had significantly higher levels of serum Pyd compared to healthy controls. The serum Pyd levels had significant correlation with radiographic joint erosions which reflected disease damage.